A Case of Unusual Visceral Heterotaxy Syndrome with Isolated Levocardia - Jo, Dae Sun (The Korean Society of Cardiology, 2013)
Situs inversus of the abdominal organs in the presence of normally placed heart on the left side of the thorax is known as situs inversus with isolated levocardia. This rare condition is commonly associated with severe congenital defects of the heart. We report a case of situs inversus with levocardia in a 19-year-old asymptomatic male patient with completely normal heart on the left chest. Spiral computed tomography of the thorax and abdomen and echocardiographic studies revealed situs inversus of abdominal organs, normal heart (levocardia), mirrored left lungs, a midline liver, a left-sided inferior vena cava connecting to the right atrium, multiple splenic masses in the abdominal right upper quadrant, and aneurysmal dilatation of a splenic artery.